Kajian Hubungan Tingkat Kualitas Permukiman Dengan Kondisi Kesehatan Masyarakat Di Kecamatan Gondokusuman, Kota Yogyakarta - Dinatha, Harry; , Drs. Priyono, M.Si; , Dra. Umrotun, M.Si (2015)
This research aims to (1) Examine the relationship of quality settlements with the public health in Gondokusuman. (2) Examine the distribution of the quality settlements in district Gondokusuman. Examine how the condition of the quality settlements with the methods of digitally interpretation on the satellite worlview image. This interpretation is used to tap the information in the form conditions of settlement density, patterns of the layout of the building, trees patron, the width of the driveway, condition of driveway, and location of the settlement. Ability of digitally Interpretations on image is limited can be assisted with survey methods to get conditions of flood, sanitation, the quality of drink water, landfills, and rain water channels that are present in the field. The results of the quality settlements from overlay all the parameters, then examined relation towards the public health conditions assisted with correlation analysis to strengthen the relations of the two variable how intertwined. The findings of this research is the study of the relationship between two variables, namely the quality settlements and public health conditions are indeed interrelated so it appears a foregone conclusion that public health conditions in District Gondokusuman is influenced by the quality of the neighborhood